Uso de material concreto no ensino do conceito de conjunto e as suas operações - Seixas, Raimundo Juscelino Dinis (Brasil, 2024)
The teaching and learning process in the field of Mathematics, and its success in shaping citizens capable of participating in academic, economic, political, and cultural life, are directly linked to classroom methodology and practice. Thus, the methodology of manipulating concrete materials associated with Sets can be a successful technique in teaching Mathematics in high school. This study aimed to analyze the contributions of manipulating concrete materials to assist in the teaching and learning process of the concept of sets. The study involved 24 students in the 2nd year of high school at a public school. The activities were designed to explore everyday situations, stimulating the development of logical reasoning and critical thinking. A qualitative approach was adopted, consisting of practical activities and a questionnaire to assess students' prior knowledge and interest in learning Mathematics. From the study, it was found that it is essential to understand the challenges faced by students and provide means to facilitate the construction of mathematical knowledge, regardless of the content taught by the teacher. It is also important to value the world knowledge that students bring with them. Additionally, the use of the methodology of concrete materials in the context of teaching the concept of Sets promotes the development of an innovative, creative, and autonomous spirit among students, contributing to the learning of Mathematics.